Nilai-Nilai Sosial dalam Novel Bidadari Untuk Dewa karya Asma Nadia - Eka Karina Kurnia Sari; Misra Nofita; Asih Ria Ningsih (Jurnal Bahasa dan Sastra, 2020)
Popular novels are often underestimated because they are considered dry with valuable life values for their readers. This study aims to describe the social values contained in Asma Nadia’s novel Bidadari untuk Dewa. This type of research is a qualitative study using descriptive methods. The social values that were used as references in this study are those stated by Zubaedi (2012). The results showed that the three social values such as love, responsibility and life harmony were exist in the novel. The most dominant social value found is the value of caring for others which is included in the value of affection (Love). This is in line with the main message in the novel, which is to help others.